Koeajoja: Auton käyttöönotto Suomessa 1900-1918 - Valta, Reijo (2021)
In Finland the use of automobiles started at the beginning of 20th century, which was later than in the neighbouring countries. This was partly due to the fact that local roads were not well suited for this new mode of travel, and in Finland there was also a reluctance to replace horse travel with this new means. The first Finnish automobile import company, the Turku-based Ab Victor Forselius Oy, tried to introduce automobiles to be used in conjunction with the city trams in Turku, as well as with the coach system in the entire country. Neither suggestion generated much interest. By 1905 the automobile and its potential uses had become more widely known through the media, and people were beginning to see the car as quite useful or even as a source of livelihood; it would enhance the freedom of movement and, in comparison to other modes of transport, it would double the speed of travel. The spring 1906 saw an increase in applications for professional taxi permits. Any further development in automobile use in Finland was, however, interrupted by the First World War. Most of the vehicles owned by Finns were expropriated by the Russian army for their own use. This resulted in coaching services and private car use, which had been started before the war, in being considered merely as test drives. However, wider public discussions about automobile users and their role in the city and road traffic had been initiated. Previous to the introduction of the car, traffic regulations had been locally stipulated within each city and county. With more cars expected on the roads, it was seen that unified, country- wide regulations would need to be in place. This novel mode of transport entering the public space triggered emotional as well as opinionated responses, which resulted in action at different levels of society. The articles and the introduction of the dissertation discuss this socio-technical change from different perspectives. For example, there is an examination of the interest of professional coaching service providers towards the use of the car. There is research into the hopes articulated through science fiction for this new mode of transport, and there is an investigation of the efforts made in northern parts of the country to improve mobility as well as a look into the safety of Helsinki as a residential area.